RADICAL CHANGES IN CONVENTIONAL TECHNIQUE OF LARYNGEAL SURGERY BY LASER - Bugti, Altaf Hussain (Journal of Ayub Medical College Abbottabad, 1996)
A review of laser surgery in laryngeal disease is made. Of special interest are patients suffering from benign laryngeal conditions such as papilloma, laryngeal polyps, etc. Laser is also of good value in early cases of laryngeal carcinoma, specially so in cases o f T I